(untitled) (Bangladesh Journal of Botany, 2022)
Genetic diversity of Ralstonia solanacearum, on seeds of tomato and brinjal from different seed sources in Bangladesh were studied with Random Amplified Polymorphic DNA (RAPD) marker. The primers viz., OPA02, OPA08, OPA09, OPA10, OPA18 and OPE19 were used in this study and were also evaluated on the basis of intensity and resolution of the band. The genetic variations in 24 isolates of R. solanacearum were analyzed with (OPA18) RAPD marker in Polymerase Chain Reaction (PCR). The percentage of polymorphic loci was 100.00 for both tomato and brinjal. Combined Dendrogram based on Nei’s (1972) genetic distance in Unweighted Pair Group Method of Arithmetic Means (UPGMA) segregated the 24 isolates of R. solanacearum into two main clusters: RsT-6, RsB-2 and RsB-3 in cluster 1, and rest of the 24 isolates were grouped in cluster 2. The isolate of brinjal (RsB-8) was close to the isolate RsB-12 and the isolate RsB-11 was near to RsT-5 (tomato) with the least genetic distance (0.000), while the brinjal isolate RsB-4 was also close to RsB-5 with the low genetic distance (0.0606). The coefficient of gene differentiation (Gst) was obtained at 1.0000 which reflects the existence of higher genetic variations among 24 isolates of R. solanacearum. Comparatively higher genetic distance (1.7346) and the lower genetic identity (0.1765) were observed in RsB-1 vs. RsT-12, whilst the higher genetic identity (1.000) and the lower genetic distance (0.000) were estimated in RsB-8 vs. RsB-12 and RsB-11 vs. RsT-5, respectively. Consequently, interactive significant genetic variations in 24 isolates of R. solanacearum of tomato and brinjal seed sources were found to be evident in both the crop species’ of diversified different varieties as the genetic variability of specific crop species. Bangladesh J. Bot. 51(3): 519-526, 2022 (September)